EFFECTIVE MANAGEMENT OF VRASANA KACCHU - CASE REPORT - H.A, *Ashwini; M. Goud, Kiran.; S J, Lolashri (International Journal of Ayurveda and Pharma Research, 2018)
Skin is an organ which represents some inner abnormalities and stress conditions within one’s body. Skin is just like a mirror reflection and manifesting various type of inner abnormality or diseased condition. Now a day’s, skin infections are more common in a persons who is having altered life style, lack of physical exercise, unhygienic condition, mental stress, irregular food habits. In Ayurveda, major skin diseases have been classified under the heading of Kustha. Acharya Sushrutha explained Vrsanakacchu under Kshudrarogas, while explaining the Nidanas, he opines that due to lack of hygiene there will be Mala sanchaya in the Vrshana leads to Kandu, Kshipraspota and Sravayukthavyadhi called Vrsanakacchu. In modern science this condition is termed as “Tinea Cruris, but in this present case, symptoms are seen in other places also, so in this condition can also be considered as “Tinea corporis" Inspite of all the advancement in treatment the results in contemporary science are not much beneficial. Here, a case report of 24 years female who approached to OPD of SKAMC,H & RC with chief complaints of dryness, blackish discoloration along with itching and peeling off of the greyish skin in the groin region, upper back, and above the umbilicus since 1 year, was treated with initial line of Bahirparimarjana chikitsa followed by Shodhana chikitsa.